Criminal Law Review of Violent Acts in the Teaching and Learning Process Based on Indonesia’s Child Protection Law of 2014 - Nurmala Nurmala (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
The phenomenon of violence still often occurs in the world of educationin Indonesia. In the process of teaching and learning activities, violenceagainst children often occurs, therefore a law is needed that canprotect children from violence. The purpose of this study is to determinethe forms of violence against children that often occur in the teachingand learning environment and to determine how legal protectionfor children is according to Law Number 35 of 2014 concerningtheamendment to Law Number 23 of 2002 concerning child protection. This research method is This study uses a type of qualitativefieldresearch, namely a type of research that describes qualitativelytheobject being discussed according to the reality in the field. Qualitativeresearch is a research that uses a natural setting, with the intentionof interpreting the phenomena that occur in depth and is carriedout byinvolving various existing methods with the research approach usedisanormative legal approach to issues concerning the synchronizationof regulations issued by schools regarding legal protection against childviolence or regulations made in the form of student code of conduct books with statutory regulations Number 35 of 2014 concerningchildprotection, which is presented descriptively, namely by describingapolicy related to the synchronization of school regulations with theChildProtection Law. With the results of the study, namely 1) Formsof violence in the teaching and learning process can be physical andnon-physical violence, involving various actions such as beatings, slapping, kicking, insults, threats, teasing, cyber bullying, hazing, and persecution. 2) Law Number 35 of 2014 significantly strengthens legal protectionfor children by establishing a prohibition on violence, regulating ix mechanisms for preventing and handling acts of violence whichisanamendment to Law Number 23 of 2002.